Kajian Teologis terhadap Pengaruh Postmodernisme dalam Gereja - Agustina Pasang (JURNAL TEOLOGI GRACIA DEO, 2021)
The emergence of the era of Postmodernism marked the end of the modern era and at the same time rejected all modern thought because it was considered old-fashioned and incompatible with today’s developments. The spirit of the era of Postmodernism is marked by progress in all areas of human life, both technology, science, as well as philosophy, theology, and religion. The purpose of this paper is to understand the theological study of Postmodernism and its impact on the church. This research uses a descriptive research method with a literature review approach, namely finding facts with the right interpretation of various literature and the results of research needed in writing the existing topic from various literature and the results of research needed in writing the spelling of exciting topic. Conclusion: Postmodernism poses a serious threat to the church because it adheres to the principle that truth is subjective and determined by individuals which is a person’s personal right, there is no absolute and final truth because everything is relative, meaning that the Word of God is no longer absolute truth and Jesus is not the only truth, only Saviour. This means that Postmodernism is contrary to the Bible which is a source of teaching for Christianity. AbstrakLahirnya era Postmodernisme menandai berakhirnya era modern sekaligus menolak semua pemikiran modern karena dianggap kolot dan tidak sesuai dengan perkembangan masa sekarang. Semangat era Postmodernisme ditandai dengan adanya kemajuan di segala bidang kehidupan manusia, baik teknologi, ilmu pengetahuan, juga dalam filsafat, theologi dan agama. Tujuan penulisan ini adalah untuk memahami kajian teologis terhadap Postmodernisme dan pengaruhnya bagi gereja. Adapun penelitian ini menggunakan metode penelitian deskriptif dengan pendekatan kajian literature yakni pencarian fakta dengan interpretasi yang tepat dari berbagai literatur dan hasil dari suatu penelitian yang diperlukan dalam penulisan topik yang ada. Kesimpulan: Postmodernisme menjadi ancaman serius bagi gereja karena berpegang pada prinsip bahwa kebenaran bersifat subjektif dan ditentukan oleh individu yang merupakan hak azasi pribadi seseorang, tidak ada kebenaran mutlak dan final karena semuanya relatif, itu berarti Firman Allah bukan lagi kebenaran  mutlak dan Yesus bukan satu-satunya Juruselamat. Artinya Postmodernisme bertolak belakang dengan Alkitab yang menjadi sumber pengajaran bagi Kekristenan.